2013
DOI: 10.1016/j.eats.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Ligamentum Teres Reconstruction

Abstract: The ligamentum teres (LT) has been studied since the 19th century, and its anatomy and biomechanical function have been well described. Recent advancements in hip arthroscopy have caused increased awareness of LT pathology. Previous reports have estimated the incidence of LT tears during hip arthroscopy to be 4% to 51%, and LT tears have been estimated to be the third most common reason for hip pain in athletes. Biomechanical studies have shown the LT's role in stability of the hip. Despite the growing body of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 9 publications
3
35
0
Order By: Relevance
“…10,[26][27][28] However, few studies have reported whether osteochondral lesions persist or progress even after ligamentum teres reconstruction. To investigate whether ligamentum teres reconstruction can not only reproduce normal hip mechanics but also prevent degenerative arthritis is a subject for future analysis.…”
Section: Discussionmentioning
confidence: 98%
“…10,[26][27][28] However, few studies have reported whether osteochondral lesions persist or progress even after ligamentum teres reconstruction. To investigate whether ligamentum teres reconstruction can not only reproduce normal hip mechanics but also prevent degenerative arthritis is a subject for future analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Our results were consistent with prior results and we found the LT test to be an effective tool in detecting LT tears at the outpatient clinic. LT tears associated with symptoms of instability, increased external rotation of the involved hip [23], or tears with accompanying hip joint pathology such as labral tears, patulous capsular tissue, or femoroacetabular impingement may be candidates for reconstruction [24]. Debridement for LT tears is widely considered in current practice; Byrd and Jones [8] and Haviv and O'Donell [25] have reported satisfactory results for debridement.…”
Section: Discussionmentioning
confidence: 99%
“…This is the least stable position of the joint. The effect of LT on hip stability in dysplastic hips and hyperlaxity has been emphasized before [4][5][6]. In their study Martin et al reported that patients with resected LT had feelings of instability and discomfort [5].…”
Section: Introductionmentioning
confidence: 99%
“…[LARS], Arcsur-Tille, France) 7 , allografts 25 , a doublestranded semitendinosus autograft 26 , and an iliotibial (IT) band tendon autograft 19 . In the only case series reporting outcomes of LT reconstruction, Philippon et al 19 performed arthroscopic reconstruction of the LT using an IT band autograft in four patients.…”
Section: Reconstruction Of the Ligamentum Teresmentioning
confidence: 99%